Trichloroacetic acid (80%) as a chemical debridement method for chronic venous leg ulcers—A pilot study. Issue 3 (15th January 2018) - Pinheiro, Rita R; Duarte, Bruno; Cabete, Joana
Abstract : Debridement is essential for the optimal care of venous leg ulcers. Several debridement methods with different limitations may be deployed. Trichloroacetic acid (TCA) is used for several dermatological purposes. Its application as a chemical debridement method for leg ulcers has never been explored. We designed a prospective study to determine the role of 80% TCA solution as a chemical debridement method for leg ulcers, regarding efficacy and procedure‐associated pain. Chronic venous leg ulcers were treated with 3 cycles of 80% TCA solution or curettage over 1 week. Pain and the mean percentage of fibrin and devitalized tissue covering wound bed were evaluated. At the end of the study, a trend towards larger fibrin mean reduction among the TCA treated ulcers was observed, although this difference was not statistically significant ( P = .35). The mean pain score after TCA application was significantly reduced compared to pain after curettage alone ( P < 0.001). TCA presented several advantages over mechanical debridement: it is a more selective debridement method, has haemostatic properties, and a simpler and faster application. The 80% TCA solution may be a cheap, simple, and considerably less‐painful chemical debridement method for venous leg ulcers compared to classical mechanical debridement.